A Review on the Application and Limitations of Administrative Health Care Data for the Study of Acute Kidney Injury Epidemiology and Outcomes in Children - Ulrich, Emma H.; So, Gina; Zappitelli, Michael; Chanchlani, Rahul (Frontiers in Pediatrics, 2021)
Administrative health care databases contain valuable patient information generated by health care encounters. These “big data” repositories have been increasingly used in epidemiological health research internationally in recent years as they are easily accessible, cost-efficient, and cover large populations for long periods of time. Despite these beneficial characteristics, it is also important to consider the limitations that administrative health research present, such as issues related to data incompleteness and the limited sensitivity of the variables. These barriers potentially lead to unwanted biases and pose threats to the validity of the research being conducted. In this review, we discuss the effectiveness of health administrative data in understanding the epidemiology of and outcomes after acute kidney injury (AKI) among adults and children. In addition, we describe various validation studies of AKI diagnostic or procedural codes among adults and children. These studies reveal challenges of AKI research using administrative data and the lack of this type of research in children and other subpopulations. Additional pediatric-specific validation studies of administrative health data are needed to promote higher volume and increased validity of this type of research in pediatric AKI, to elucidate the large-scale epidemiology and patient and health systems impacts of AKI in children, and to devise and monitor programs to improve clinical outcomes and process of care.